THE USE OF PEER REVIEW TO IMPROVE FBIB STUDENTS’ SPEAKING SKILL - Agnes Widyaningrum (Universitas Stikubank (UNISBANK) Semarang, 2017)
Students of English Department should know how to learn and practice using English. They should understand ways to help them improve their English skills. Among those four English skills namely speaking, listening, reading and writing, the most difficult one to master is writing. This study will not focus on writing but on speaking skill. The subject of the study is FBIB Students who took the subject called Business Transactional Conversation.The students sometimes have difficulty to improve their speaking skill because they are rarely use English in their daily talk with their peers. They use English when they have lecture and talk with their lecturers. The reason why they are rarely use English when they talk with their peers because they are afraid of making mistakes and being laughed by their peers. It will influence their motivation to speak English.The students’ motivation to learn and then master English is a positive trigger to monitor their English skill. A good idea of having peer review in spoken class is a way to help students improve their speaking skill. The result is satisfactory enough because they are more comfort to be evaluated by their own peer than by the lecturer. This peer review is one of some alternatives to help English learners improving their English skill.This study belongs to classroom reasearch since the lecturers who are also the researchers conducted research for one semester for the fourth semester students who belong to morning program. The number of students who are being observed is 14 students. The researchers collected the data with the help of a student from the observed class. The data are qualitative data in the form of peer review rubric, teacher’s journals, teacher’s interpretation and teacher’s triangulation. After the students do peer review individually as well as in group, their motivation increased and their speaking skill improved accordingly. In addition, by conducting classroom research the lecturers can improve student learning because they know what works best for their students in particular situation.Keywords : English skills, speaking skill, spoken class, peer review